The New Edge of Indian Cinema: An Analysis of the Treatments of Gender, Sexuality, and Matrimony in the New Indian Cinema in English - Dasgupta, Satarupa (Asian Cinema, 2006)
Traditionally, there have been two schools of Hindi cinema. The center stage has always been occupied by Bollywood, which enthralls the Indian audiences globally with “song-and-dance extravaganzas and melodramatic stories big on family values; the other was the “Satyajit Ray-inspired realistic art-house films, which flowered in the 1970s and 1980s,” and which “tried to create a distinct language of film, but their work was relegated to festivals and television, where it wilted in the wings…” (Chopra, 2005). However, a particularly noticeable trend in the Indian movie industry in recent years has been the emergence of a third type of cinema -- the new Indian cinema in English.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4xNy4xLjEzOF8x